Granulomatosis with Polyangiitis with Ocular Manifestations - Lukpan Orazbekov; Botagoz Issergepova; Makpal Assainova; Kairat Ruslanuly (Case Reports in Ophthalmology, 2021)
Granulomatosis with polyangiitis (GPA) is a granulomatous-necrotic systemic vasculitis with a lesion of predominantly the upper and lower respiratory tracts at the onset of the disease (vasculitis, accompanied by granulomatous inflammation), and subsequently renal (glomerulonephritis). In addition, GPA may manifest as inflammation of small arteries and veins. Despite many years of study of this disease, the etiology of GPA remains unknown. The present case is about a 47-year-old female, who had been suffering from necrotizing scleritis, corneal ulcer, and secondary glaucoma in both eyes for 3 months, and she was treated with anti-inflammatory and antimicrobial therapy that showed no effect; the patient’s general condition became worse. In the second week of treatment, multiple abscess ruptures exposed the sclera. Sampling of the affected conjunctival tissue and positive HLA B8 haplotype and ANCA (PR3-ANCA) testings make it clear that GPA was the main reason of necrotizing scleritis with inflammation. The targeted treatment of the underlying disease allows to stabilize an inflammation of corneal and scleral lesions.